Joshua Fragment from Codex Climaci Rescriptus: A New Edition Based on the Multispectral Images. - Malik, Peter (Vetus Testamentum, 2023)
This article offers a new edition of the LXX Joshua portion of Codex Climaci Rescriptus, an important, though somewhat neglected, Sinaitic Palimpsest. The edition is based on the post-processed multispectral images, produced by Early Manuscripts Electronic Library in cooperation with the Lazarus Project. The new technology has aided in correcting various errors in the editio princeps and uncovering hitherto unseen textual and paratextual elements. Moreover, the results of radiocarbon analysis have been factored into the dating of the fragment, resulting in a new proposal for its date of origin.